The AICHR Framework for Action - Cook, Alistair David Blair (2018)
On 23 October 2009, ASEAN formally launched the ASEAN Intergovernmental Commission on Human Rights at the 15th ASEAN Summit in Thailand. The ASEAN leaders also announced the ‘Cha-am Hua Hin Declaration on the Inauguration of the AICHR’. In the Declaration, member states pledged full support to the new ASEAN body and emphasized their commitment to further develop cooperation to promote and protect human rights in the region. This Insight investigates current developments at the national, regional and international levels and how these developments can assist in formulating a framework for action for the new regional human rights body.